Option Market Activity - Lakonishok, Josef; Lee, Inmoo; Pearson, Neil D.; Poteshman, Allen M. (Review of Financial Studies, 2007)
[This article uses a unique option data set to provide detailed descriptive statistics on the purchased and written open interest and open buy and sell volume of several classes of investors. We also show that volatility trading through straddles and strangles accounts for a small fraction of option trading volume and presents evidence that a large percentage of call writing is part of covered call positions. Finally, we find that during the stock market bubble of the late 1990s and early 2000 the least sophisticated investors in the data set substantially increased their purchases of calls on growth but not value stocks.]